(untitled) (Medico Legal Update, 2020)
Leprosy (Morbushansen) is a chronic infection disease caused by Mycobacterium leprea that firstly attack peripheral nervous then the skin, mucosamembrane, upper respiratory track, eyes and others body tissue except central nervous system. The province of West Papua have the largest number of leprosy in Indonesia. This number is shocking and make people worried. Data from public health office of West Papua province discovered as much as 607 cases of leprosy was found in West Papua distributed in many areas. From that data, West Papua province in 2015 was selected as endemic categories. The purpose of this research was to know the affect of information education using pocket book and audio visual to knowledge increase on leprosy and prevention behavior on leprosy patient at Malanu public health center working area sorong city. Research design used was “Quasi experimental pre-post test design” with audio visual and pocket book intervention. This design used to learnt about “caused-effect correlation” framework phenomenon with giving intervention or manipulation on research subject, and then learn the effect of the intervention. Population in this research was all patient with leprosy at Malanu Public Health Center working area. Total sample in this research was 20 people for each group using purposive sampling technique, purposive sampling technique is a choosing a group of subject based on certain characteristic that has a strong bond with population characteristic that have been known before. The affect analysis of information education to knowledge increase on leprosy after intervention was meaningfully increase than before intervention as much as 0,000 (p value <0,05). Conclusion, there was a significance affect to respondent’s knowledge increase after intervention.